2012
DOI: 10.1007/s00540-011-1294-1
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermic cardiopulmonary bypass for minimally invasive mitral valve plasty in adult moyamoya disease

Abstract: A 43-year-old man underwent minimally invasive mitral valve plasty of a flail mitral valve. Four years previously, he had been diagnosed with moyamoya disease (MMD) by cerebral magnetic resonance imaging/angiography findings. In MMD, risk factors for cerebral stroke include changes in arterial carbon dioxide partial pressure, blood pressure, and body temperature. And during cardiopulmonary bypass (CPB), these hemodynamic changes can be challenging. However, hypothermia during CPB can decrease cerebral oxygen c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…When regional cerebral oxygen desaturation continues during sevoflurane general anesthesia in patients with MMD, it might be efficacious to administer intravenous anesthetics concurrently. These management procedures limited the fluctuation of rSO 2 values to within 17 % in our patient, which was nearly equal to that in a previous study [ 3 ], and prevented the development of cerebral deficits.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…When regional cerebral oxygen desaturation continues during sevoflurane general anesthesia in patients with MMD, it might be efficacious to administer intravenous anesthetics concurrently. These management procedures limited the fluctuation of rSO 2 values to within 17 % in our patient, which was nearly equal to that in a previous study [ 3 ], and prevented the development of cerebral deficits.…”
Section: Discussionsupporting
confidence: 77%
“…De Buysscher et al [ 4 ] also reported that conversion from a non-pulsatile flow to a pulsatile flow resulted in a gradual increase in rSO 2 values as opposed to a sudden decrease in rSO 2 in an adult MMD patient undergoing CPB. In addition, Cheul-Hong et al [ 3 ] reported up to 15 % fluctuations in rSO 2 values during cardiac surgery in an MMD patient who was later discharged from the hospital without any complications. In pediatric patients undergoing CPB, pulsatile flow has advantages over nonpulsatile flow as measured by near-infrared spectroscopy and transcranial Doppler ultrasound, which may improve postoperative neurodevelopmental outcomes [ 7 ].…”
Section: Discussionmentioning
confidence: 99%